Edukasi Mewujudkan Generasi Emas Digital Society Dengan Quality Education Kebangsaan Di MA Daarul Hikmah Sungai Rengit Kabupaten Banyuasin - Ivana; Diah Putri Islamy; Abizar Asmail (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Theme of education Quality Education National is supporting a large theme of KKN Stisipol Candradimuka XXVII in 2023 namely Digital Society. Digital society carries 17 themes in order to support SDGs programs that are sustainable development goals. Indonesia is one of 190 countries in the world that supports and agreed to SDGs that if interpreted is the goal of sustainable development. One of the theme of SDGs is a quality education. The purpose of this educational activity is the national education character of the Indonesian gold generation. This educational activity is carried out in MA Daarul Himmah Sungai Rengit  Regency Banyuasin The method of implementing this educational activity is a seminar in the form of lectures, discussions and question and answer. This educational activity runs smoothly and organized. Where these educational participants are very enthusiastic to answer questions submitted and answer all questions properly and correctly. In addition, participants are also passionate to provide questions about nationality given that is about Pancasila and Bhineka Tunggal Ika. The participants who answered the question and which gave questions get rewarded from the committee in the form of gifts and plaques.